2022
DOI: 10.3389/fmars.2022.901348
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping at the Speed of Light: Distributed Acoustic Sensing of Baleen Whales in the Arctic

Abstract: In a post-industrial whaling world, flagship and charismatic baleen whale species are indicators of the health of our oceans. However, traditional monitoring methods provide spatially and temporally undersampled data to evaluate and mitigate the impacts of increasing climatic and anthropogenic pressures for conservation. Here we present the first case of wildlife monitoring using distributed acoustic sensing (DAS). By repurposing the globally-available infrastructure of sub-sea telecommunication fiber optic (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Using data from the same experiment, Bouffaut et al 15 demonstrated the capacities of DAS for acoustic monitoring of baleen whales. Whale detections were made out to at least 95 km along the cable, and the analysis identified call types from at least two low-frequency baleen whale species: North Atlantic blue whale ( balaenoptera musculus ) and fin whale ( balaenoptera physalus ), with a number of stereotyped North Atlantic blue whale signals (AB call, peak frequency at Hz; arched sounds, 9-Hz call 28 ) and mid-frequency down-sweeps (peak frequency Hz, average duration s).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using data from the same experiment, Bouffaut et al 15 demonstrated the capacities of DAS for acoustic monitoring of baleen whales. Whale detections were made out to at least 95 km along the cable, and the analysis identified call types from at least two low-frequency baleen whale species: North Atlantic blue whale ( balaenoptera musculus ) and fin whale ( balaenoptera physalus ), with a number of stereotyped North Atlantic blue whale signals (AB call, peak frequency at Hz; arched sounds, 9-Hz call 28 ) and mid-frequency down-sweeps (peak frequency Hz, average duration s).…”
Section: Resultsmentioning
confidence: 99%
“…The increased spatial coverage and bandwidth offered by the recent generation of DAS instrumentation enabled studies of water-borne acoustic sources 11 . Rivet et al 12 demonstrated the possibility of monitoring near-surface acoustic sources from ships in the Mediterranean sea, Taweesintananon et al 13 and Matsumoto et al 14 compared DAS-recorded seismic airguns to traditional instrumentation, and Bouffaut et al 15 demonstrated the potential of DAS to monitor baleen whales. These studies revealed that the large number of sensors allows a high antenna gain from coherent processing, dramatically increasing the signal-to-noise ratio (SNR), while the long spatial extent allows near-field beamforming to focus on sources, delivering not only bearing but potentially range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sladen 2021), on the other hand, used a bubble gun seismic source to obtain near-surface shear velocity structure of seafloor sediments by active source method [8,9]. Additionally, DAS also has potentials to ship detection and marine creature monitoring [10,11]. This article demonstrates the deep-sea noise monitoring ability of DAS system.…”
Section: Introductionmentioning
confidence: 88%
“…Worthy of mention, in ocean environment, is the wildlife monitoring of baleen whales in the Arctic us-ing DAS that employs the globally available infrastructure of sub-sea telecommunication fiber optic cables [Bouffaut et al, 2022].…”
Section: Distributed Acoustic Sensingmentioning
confidence: 99%